Priming integrin α5 promotes human dental pulp stem cells odontogenic differentiation due to extracellular matrix deposition and amplified extracellular matrix‐receptor activity. Issue 8 (17th December 2018) - Wang, He; Ning, Tingting; Song, Ci; Luo, Xinghong; Xu, Shuaimei; Zhang, Xiaoyi; Deng, Zilong; Ma, Dandan; Wu, Buling
Abstract: Our previous study showed that knocking down integrin α5 (ITGA5) expression by using a lentiviral vector in human dental pulp stem cells (DPSCs) led to weakening proliferation and migration capacity while enhanced odontogenic differentiation. To seek for possible clinical application, we investigated the effect of the ITGA5 priming synthetic cyclic peptide (SCP; GA‐CRRETAWAC‐GA) on proliferation, migration, and the odontogenic differentiation of DPSCs. Remarkably, the involved mechanism was explored by isobaric tag for relative and absolute quantitation proteomic technique, and the in vivo effect of ITGA5 was investigated by nude mice subcutaneous transplantation of cell and hydroxyapatite/β‐tricalcium phosphate complex. Results showed that SCP weakened the proliferation and migration capacity while enhanced odontogenic differentiation of DPSCs as lentivirus. The phosphorylation of FAK, PI3K/AKT, and MEK1/2/ERK1/2, along with IGF2/IGFBP2 and Wnt/β‐catenin signaling pathway play an important role in this process. Proteomic Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis revealed the key role of extracellular matrix (ECM) and ECM‐receptor activity pathway were involved. ECM constituents, secreted protein acidic and cysteine‐rich (SPARC), lumican, vitronectin, prolargin, decorin, collagen type VI α1 chain (COL6A1), COL6A2, COL14A1, and COL5A1 were upregulated in the ITGA5‐silenced group. Inhibited expression of ITGA5 in DPSCs increased osteoid tissue formation and stronger related genes expression in vivo. In conclusion, the ITGA5 priming peptide could promote DPSCs odontogenic differentiation as lentivirus. Proteomics and bioinformatic analysis revealed that this may be due to the deposition of ECM and amplified ECM‐receptor activity, which could fuel the application process of utilizing priming ITGA5 on dental clinical practice. Abstract : The present study deepened our understanding of integrin α5 (ITGA5) and dental pulp stem cells (DPSCs), which set an example of regulating stem cell differentiation via a specific gene‐target strategy. As an "inside‐out" signaling, the priming ITGA5 effect on DPSCs caused extracellular matrix deposition, which targeted other integrin members, while the "outside‐in" signaling led to the phosphorylation of FAK, PI3K/AKT, MEK1/2/ERK1/2, along with IGF2/IGFBP2 and Wnt/β‐catenin signaling changes, and the amplified extracellular matrix (ECM)‐receptor activity from other integrin members, promoted the odontogenic differentiation of DPSCs.